2021
DOI: 10.1101/2021.04.15.440048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A direct lateral entorhinal cortex to hippocampal CA2 circuit conveys social information required for social memory

Abstract: The storage of information by the hippocampus in long-term memory is thought to involve two distinct but related processes. First, the hippocampus determines whether a given stimulus is novel or familiar; next, the hippocampus stores the novel information in long-term memory. To date, the neural circuits that detect novelty and their relation to the circuits that store information of a specific memory are poorly understood. Here we address this question by examining the circuits by which the CA2 region of the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…The goal of this study was to investigate mitochondrial heterogeneity in the mouse hippocampus. Focusing on the enrichment of MCU in area CA2, we unexpectedly uncovered that MCU expression is preferentially enriched in CA2 distal apical dendrites, precisely where CA2 neurons receive layer-specific input from entorhinal cortex II, a circuit recently shown to carry social information to CA2 (Lopez-Rojas et al 2022; Dang et al 2022). This striking enrichment of MCU in CA2 distal dendrites compared to CA2 proximal dendrites and neighboring CA1 dendrites is not seen with another mitochondrial marker, COX4, suggesting that mitochondria in CA2 distal dendrites have a unique molecular expression profile.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The goal of this study was to investigate mitochondrial heterogeneity in the mouse hippocampus. Focusing on the enrichment of MCU in area CA2, we unexpectedly uncovered that MCU expression is preferentially enriched in CA2 distal apical dendrites, precisely where CA2 neurons receive layer-specific input from entorhinal cortex II, a circuit recently shown to carry social information to CA2 (Lopez-Rojas et al 2022; Dang et al 2022). This striking enrichment of MCU in CA2 distal dendrites compared to CA2 proximal dendrites and neighboring CA1 dendrites is not seen with another mitochondrial marker, COX4, suggesting that mitochondria in CA2 distal dendrites have a unique molecular expression profile.…”
Section: Discussionmentioning
confidence: 93%
“…This is consistent with the asymmetric pattern of MCU-labeled mitochondrial morphology in CA2 dendrites. Notably, input from the LECII, but not the MECII, carries social information relevant to social recognition memory (Lopez-Rojas et al 2022). Taken together, CA2 SLM may have higher expression of MCU and greater mitochondrial mass than CA1 SLM in order to metabolically support more numerous and more active synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, DGC recruitment of FFI in CA3/CA2 is randomly wired so as to provide blanket inhibition and govern network excitability in CA3 and CA2, rather than couple individual DGC-dependent excitation with inhibition onto distinct populations of pyramidal neurons (Neubrandt et al, 2017). Loss of PV IN mediated inhibition may disrupt neuronal ensembles and network oscillations by impairing neuronal spiking, recurrent excitation in CA3 networks (Sadeh and Clopath, 2021), reciprocal inhibition between CA3 and CA2 (Boehringer et al, 2017;Fernandez-Lamo et al, 2019;Lehr et al, 2021;Middleton and McHugh, 2020;Nasrallah et al, 2019;Stober et al, 2020) and/or the balance between subcortical and entorhinal inputs to CA3/CA2 during encoding of social stimuli (Chen et al, 2020;Lopez-Rojas et al, 2022;Robert et al, 2021;Wu et al, 2021). Future studies will edify how PV inhibition of CA3/CA2 facilitates encoding of social stimuli in CA3 and CA2 neuronal ensembles and network oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…Dentate gyrus (DG)-CA3/CA2 circuits play a critical role in encoding social experiences by integrating sensory information from association cortices, entorhinal cortex, prefrontal cortex and subcortical sites (Alexander et al, 2018;Alexander et al, 2016;Chen et al, 2020;Cope et al, 2022;Finlay et al, 2015;Gangopadhyay et al, 2021;Hitti and Siegelbaum, 2014;Lehr et al, 2021;Lin et al, 2018;Lopez-Rojas et al, 2022;Meira et al, 2018;Montagrin et al, 2018;Oliva et al, 2016;Oliva et al, 2020;Raam et al, 2017;Schafer and Schiller, 2018a, b;Stevenson and Caldwell, 2014;Tavares et al, 2015;Tuncdemir et al, 2022;Woods et al, 2020). Prior work has shown that experience or learning increases dentate granule cell (DGC) recruitment of parvalbumin inhibitory neurons (PV IN) mediated perisomatic inhibition of CA3 neurons (Guo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Visuosocial memory can be defined as one kind of social memory which contains visual information associated with social context. One potential brain region to store visuosocial memory is the hippocampus because; 1) Hippocampus has been considered as a key brain region to associate different types of information such as space, object, sound cues, and context into episodic memory [3][4][5], and 2) Recently the CA2 hippocampus was suggested as the critical brain region for social memory in mouse [6,7]. Interestingly, receptors of oxytocin and vasopressin which are well-known for their function in social cognition are highly and specifically expressed in hippocampal CA2 [8,9].…”
Section: Introductionmentioning
confidence: 99%